Autophagy contributes to hypoxia-induced epithelial to mesenchymal transition of endometrial epithelial cells in endometriosis. Issue 5 (31st May 2018) - Liu, Hengwei; Du, Yu; Zhang, Zhibing; Lv, Liqun; Xiong, Wenqian; Zhang, Ling; Li, Na; He, Haitang; Li, Qi; Liu, Yi
Abstract: Endometriosis is a benign gynecologic disorder, and presents with malignant characteristics, such as migration and invasion. Hypoxia has been implicated in triggering epithelial–mesenchymal transition (EMT). Hypoxia is also known to induce autophagy. However, the relationship between autophagy and EMT under hypoxia conditions in endometriosis remains unknown. In the present study, we found that the expression of hypoxia-inducible factor-1α (HIF-1α), microtubule associated protein light chain 3 (LC3), and mesenchymal cell marker vimentin was significantly higher in ectopic endometrium from patients with endometriosis, along with decreased expression of epithelial cell marker E-cadherin. After hypoxia treatment, endometrial epithelial cells exhibited enhanced migration and invasion abilities, as well as promoted autophagy and the EMT phenotype. Our analyses also show that HIF-1α was responsible for induction of autophagy. Moreover, inhibition of autophagy by chemical or genetic approaches suppressed hypoxia triggered EMT and reduced cell migration and invasion. Collectively, our findings identify that autophagy is critical for the migration and invasion of endometrial cells through the induction of EMT and indicate that inhibition of autophagy may be a novel useful strategy in the treatment of endometriosis. Abstract : The autophagy, which is induced by peritoneal hypoxia, is essential for EMT initiation in endometriosis.